The Imports of Used KRL as Indonesia's Dependency on Japan in Electric Train Technology - Haryo Prasodjo (Universitas Muhammadiyah Malang, 2019)
Indonesia and Japan have established formal diplomatic relations since 1958 marked by the signing of a peace agreement between the two of them. The peace agreement includes a program of assistance provided by the Japanese government to Indonesia as a form of compensation for Japanese colonialism in Indonesia. This assistance program is known as Japan Official Development Assistance / ODA. Through this ODA program, Indonesia and Japan began to engage in import and procurement of used KRL fleets and make Indonesia dependent on Japan in electric train technology. By using descriptive research methods and dependence theory, this study seeks to describe Indonesia's dependency on Japan in electric train technology through KRL import cooperation which has an impact on the strengthening of Japanese dominance in Indonesia, especially in the automotive sector and will certainly affected on government policies related to this matter.